CREATING AN ADAPTIVE LEARNING ENVIRONMENT BASED ON ARTIFICIAL INTELLIGENCE AND ITS IMPACT ON THE QUALITY OF PRIMARY EDUCATION - Khojiyeva Nasiba Bakhodirovna (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
Abstract. This article analyzes the theoretical and practical impact of adaptive learning environments based on artificial intelligence technologies on the quality of primary education. The article highlights the main components of adaptive systems: dynamic assessment, personalized learning trajectories, real-time feedback, and teacher support mechanisms. It argues that the cognitive, emotional, and social development of children of primary school age should be taken into account when designing AI-based systems. It also evaluates the impact of adaptive learning on the quality of education in terms of: mastery level, motivation, reducing inequality, and changing the role of the teacher. The article also analyzes the pedagogical, ethical, and technological problems of implementing AI adaptive learning.